Educação de jovens e adultos diversidade, inclusão e conscientização - Miguel, José Carlos (Editora Oficina Universitária, 2021)
The book "Education of Youth and Adults: Diversity, inclusion and awareness" is situated in the context of a multiplicity of training processes aimed at contemplating, in addition to the quest to overcome absolute illiteracy, the debate on themes aimed at broadening the conception of EJA , which, although publicized, are rarely included in the teaching programs of this segment of basic education, such as cultural identity, differences, racial issues, power relations, gender issues, art and popular culture, among others. others, all of them lacking public policies for their implementation. It is understood as imperative the production and dissemination of knowledge involving EJA in order to consolidate it as an effective field of theoretical-practical reflections aimed at guaranteeing access and permanence of subjects in the school environment located in a true mosaic of cultures, ethnicities , living conditions and social groups, with yearnings for social development, constitute an enormous challenge for public policies. Thus, in the set of texts of the work, the theoretical foundation of several curricular components of this area of knowledge, the documentary analysis aimed at legal support and, in particular, proposals for didactic-pedagogical intervention aimed at the necessary mediation for the constitution of public policies and true citizenship education. Thus, the book is of interest for the initial training of teachers, for teachers who teach in EJA and for professionals in education networks involved with technical-pedagogical guidance and initial or continuing training of educators.